Using probe-microphone measurements to improve the match to target gain and frequency response slope, as a function of earmould style, frequency, and input level. - Munro, Kevin J.; Puri, Reema; Bird, Judith; Smith, Mark (International Journal of Audiology, 2016)
Objective:Matching a prescription gain target at 60–65 dB SPL does not ensure audibility of lower input levels, nor does it mean the fitted frequency response slope is conducive to good sound quality. The aim of the present study was to evaluate the use of probe-microphone measurements to match target gain and slope, as a function of earmould style, frequency, and input level.Design:The real-ear insertion gain was calculated for an input of 50, 65, and 80 dB SPL for the manufacturer’s ‘initial fit’ (IF) settings and after adjustment to target in 49 and 51 open slim-tube and custom earmould fittings, respectively.Study sample:One hundred adults with median age 74 years (range 32–93).Results:Some 18%–67% of the IF settings were within 10 dB of the target gain but this increased to >85% after adjustment. Some 47%–71% of the IF settings were within 10 dB of the target slope but, with the exception of 2–4 kHz, this increased to >88% after adjustment.Conclusions:The results indicate that IF settings are inadequate, at least for the model of hearing aid used in the present study; however, significant discrepancies remained, even after adjustment.